2018
DOI: 10.1016/j.jsxm.2018.04.639
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Arteriogenic Erectile Dysfunction for Coronary Artery Disease in Men

Abstract: Background Erectile dysfunction (ED) is assumed to be connected with vascular disease caused by endothelial dysfunction, and characterized by the incapability of the smooth muscle cells lining the arterioles to relax, therefore, inhibit vasodilatation. Aim To assess the predictive value of arteriogenic ED for coronary artery disease in men above the age of 40 years. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…1 Over the same period, the global prevalence of the disease among adults has risen from 4.7% to 8.5%. 1 2 3 4 5 DM exerts detrimental effects on multiple body systems including blood vessels, heart, eyes, kidneys, hormones, and nerves. 1 2 3 4 5 Moreover, it has been associated with physical, cognitive, and emotional disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Over the same period, the global prevalence of the disease among adults has risen from 4.7% to 8.5%. 1 2 3 4 5 DM exerts detrimental effects on multiple body systems including blood vessels, heart, eyes, kidneys, hormones, and nerves. 1 2 3 4 5 Moreover, it has been associated with physical, cognitive, and emotional disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 3 4 5 DM exerts detrimental effects on multiple body systems including blood vessels, heart, eyes, kidneys, hormones, and nerves. 1 2 3 4 5 Moreover, it has been associated with physical, cognitive, and emotional disabilities. 2 3 4 5 6 Erectile dysfunction (ED) represents a well-known complication of DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Montorsi et al reported that the severity of the ED correlates with the severity of the CAD [16]. Therefore, ED is consider more than merely sexual dysfunction, rather, it is considered a warning symptom and an independent predictor of CAD [1719].…”
Section: Introductionmentioning
confidence: 99%